PENGGUNAAN PARTIKEL AKHIR-KALIMAT WA OLEH PRIA DALAM KOMIK “NOBUNAGA NO SHEFU” (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The end-sentence particle „wa‟ is widely used to express feelings, because feeling activities tend to be used by women, so the final-sentence particle wa is often said to be a variety of women's language. However, in the Nobunaga no Shefu comic, there are many conversations that use „wa‟ by male characters. Therefore, an understanding of the use of particle endings „wa‟ is needed to understand the use of particle endings „wa‟ by men. This study aims to examine the use and meaning of the end-sentence particle „wa‟. The method used in this study is a qualitative method. The comic Nobunaga no shefu is used as the data source. The results of the data analysis of the use and meaning of the final particle „wa‟ from the comic Nobunaga no shefu which uses the particle ending-sentence wa by men, it was found that there was a shift in form, which basically the expression of exclamation of feeling belonging to the use of non-dialogic wa shifted to the use of wa dialogical. However, the use of the final particle „wa‟ which is an expression of exclamation of feeling can still be used. Thus the final particle wa can be used by male speakers because the use of wa is related to feelings so it can be used by any gender.Key Words: The end-sentence particle „wa‟, Use of Particle End-sentence wa, Meaning of Particle End-sentence wa.